2021
DOI: 10.3389/fimmu.2021.764825
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Eosinophils in Resolution of Arthritis

Abstract: Eosinophils are a minor component of circulating granulocytes, which are classically viewed as end-stage effector cells in host defense against helminth infection and promoting allergic responses. However, a growing body of evidence has emerged showing that eosinophils are versatile leukocytes acting as an orchestrator in the resolution of inflammation. Rheumatoid arthritis (RA) is the most common chronic inflammatory disease characterized by persistent synovitis that hardly resolves spontaneously. Noteworthy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 72 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…Therefore, it was concluded that dysregulation of SCAT biology contributes to metabolic syndrome in humans ( 70 ). A specific population of eosinophils was identified in patients with RA however a proper understanding of eosinophils and their functions in OA is still under investigation ( 71 ). A detailed study is needed to define how this innate immune cell type reacts when the joint microenvironment homeostasis is affected by this multifactorial disease.…”
Section: Role Of Innate Immunity In Obesity and Oamentioning
confidence: 99%
“…Therefore, it was concluded that dysregulation of SCAT biology contributes to metabolic syndrome in humans ( 70 ). A specific population of eosinophils was identified in patients with RA however a proper understanding of eosinophils and their functions in OA is still under investigation ( 71 ). A detailed study is needed to define how this innate immune cell type reacts when the joint microenvironment homeostasis is affected by this multifactorial disease.…”
Section: Role Of Innate Immunity In Obesity and Oamentioning
confidence: 99%
“…From a more peripheral (articular) perspective, evidence from experimental models and RA patients in remission demonstrated that arthritis resolution could be mechanistically based on enhanced induction of type 2 innate lymphoid cells (ILC2) by IL-9, which in turn elicits the activation of regulatory T cells ( 47 ). Resident eosinophils, consistently present in the synovia of patients with RA in remission, have been shown to promote arthritis resolution by secreting resolvins and switching synovial macrophages into the M2 phenotype ( 48 ). Only recently, Alivernini et al ( 49 ) provided further evidence supporting the concept of active remission.…”
Section: Pathophysiology Of Ra Flarementioning
confidence: 99%
“…RA is a systemic autoimmune disorder defined by chronic inflammation occurring within synovial joints, the main symptoms of which are restricted joint movement and deformity. Eosinophils have been confirmed to play roles in RA-associated inflammation, which is characterized by heightened serum eosinophil cationic protein levels and peripheral eosinophil count elevation at baseline and served as prognostic indicators for adverse outcomes in early-stage RA ( 35 ). Patients with RA suffering from frailty exhibited symptoms that include sarcopenia, fatigue, and low activity.…”
Section: Discussionmentioning
confidence: 99%